3D‐bulk to nanoforms of modified hydroxyapatite: Characterization and osteogenic potency in an in vitro 3D bone model system. Issue 5 (17th December 2021) - Sundar, Rebu; Joseph, Josna; Babu, Suresh; Varma, Harikrishna; John, Annie; Abraham, Annie
Abstract: Synthetic bioceramics are replacing conventional methods of treating bone defects with autografts owing to the high demand of bone substitutes, with their Surface topography and size contributing to favor cytocompatibility in tissue regeneration. This experimental study deals with the comparative evaluation of the physical characterizations of four different in‐house synthesized bioceramics from 3D‐bulk to nanoforms of hydroxyapatite (HA), Biphasic calcium phosphate (BCP), Strontium doped hydroxyapatite (SrHA) and Silica coated hydroxyapatite (HASi) and also simultaneously evaluates adhesion, proliferation and osteogenic differentiation of rabbit adipose derived mesenchymal stem cells (RADMSCs) on these biomimetic ceramic niches. The osteogenic induced cells grown on 3D scaffolds for a period of 7, 14, 21, and 28 days were analyzed for their viability (MTT, LDH, live‐dead assays), morphology (SEM), proliferation (Cytox‐Red) and osteogenic differentiation (ALP, osteocalcin expression). Cellular activities and differentiation of RADMSCs were significantly higher on SrHA indicating the role of strontium in the differentiation of mesenchymal stem cells on this ceramic platform to the bone lineage. In order to reinforce the materials for hard tissue implantation and drug delivery, nano‐SrHA (nSrHA) became the nanoparticle of choice based on its non‐toxicity, cytocompatibility and osteogenic properties (nSrHA > nHASi > nBCP > nHA).